2000
DOI: 10.1046/j.1365-2494.2000.00190.x
|View full text |Cite
|
Sign up to set email alerts
|

Setting management limits for the production and utilization of herbage for out‐of‐season grazing

Abstract: Three experiments were carried out on perennial ryegrass‐dominant swards to provide a basis for recommendations for the limits to (a) building up and timing of utilization of a herbage ‘bank’ for out‐of‐season grazing and (b) duration and intensity of early spring grazing in the United Kingdom and Ireland. In experiment 1, the effect of regrowth interval (from 7 September, 20 October, 17 November or 15 December) in autumn on herbage accumulation, leaf turnover and on subsequent spring growth was investigated. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
23
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 11 publications
8
23
0
Order By: Relevance
“…It is concluded that in the south of Ireland to achieve a given herbage mass and quality at a given point in winter, date of closing should be later in autumn than would be required in the north‐east of Ireland. The recommendations from the data at the Grange site, suggesting a 2‐month interval between closing in mid‐September for utilization 8 weeks later and resulting in about 2 t DM ha −1 above 4 cm at this time agrees with the findings of Laidlaw and Mayne (2000) from a field study carried out about 120 km further north. Although trends in response to closing date and temperature were similar between the two sites in this study, they were quantitatively different and deficiencies are exposed in the information generally available to predict the herbage mass and quality of herbage for utilization at given times throughout the winter.…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…It is concluded that in the south of Ireland to achieve a given herbage mass and quality at a given point in winter, date of closing should be later in autumn than would be required in the north‐east of Ireland. The recommendations from the data at the Grange site, suggesting a 2‐month interval between closing in mid‐September for utilization 8 weeks later and resulting in about 2 t DM ha −1 above 4 cm at this time agrees with the findings of Laidlaw and Mayne (2000) from a field study carried out about 120 km further north. Although trends in response to closing date and temperature were similar between the two sites in this study, they were quantitatively different and deficiencies are exposed in the information generally available to predict the herbage mass and quality of herbage for utilization at given times throughout the winter.…”
Section: Resultssupporting
confidence: 85%
“…The data presented here help to determine the limit to which herbage accumulated for winter grazing can remain unutilized when the sward is closed from grazing at a range of dates in autumn. A maximum of 8 weeks after closing in September agrees with conclusions reached by Laidlaw and Mayne (2000) for a similar environment.…”
Section: Discussionsupporting
confidence: 88%
“…Similar to both De Klein and Ledgard (2001) and Laidlaw and Mayne (2000), the combination of high N concentrations and increased ED during the autumn and early winter months within the current data are indicative of the increased risk of N loss during this period. Sprosen et al (2002) have also previously reported no significant SR effect on NO 3 − N losses from grazing swards in New Zealand and concluded that this was due to the lower grass DMI and an earlier end to lactation and removal of cull cows in high-SR treatments.…”
Section: Discussionsupporting
confidence: 72%
“…This is particularly evident over the winter period (December and January) when perennial ryegrass, the principal forage on Irish livestock farms, has growth and nutritional limitations for winter grazing (Brereton, 1995). Furthermore, the accumulation of large quantities of high‐quality herbage in Ireland is unlikely to be ascertained from regrowths subsequent to grazing in September (Laidlaw and Mayne, 2000). As a consequence, feed requirements exceed grass supply during the late autumn and winter period, hence providing inadequate herbage masses for winter grazing.…”
Section: Introductionmentioning
confidence: 99%